A inserção socioeconômica de mulheres negras no brasil e o mito da democracia racial - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The socioeconomic integration of black women in Brazil is marked by gender and racial inequalities, which are reflected in wages, unemployment rates, precarious conditions, and the vulnerability of this social group. The myth of racial democracy is an ideology that asserts that Brazil is a country where there is no racism or discrimination against the black population, given that all Brazilians are the result of a harmonious mixture of the different ethnic groups that formed the nation. Given this scenario, the general objective of this research is to analyze how the socioeconomic inclusion of black women in Brazil challenges the idea of racial democracy. Methodologically, this research will use a mixed method and regarding its approach, it will be quantitative and qualitative with a descriptive character. The research techniques adopted will be documentary research and secondary databases, through content analysis and descriptive statistics. The results of the research show that black women in Brazil have historically occupied the most subordinate positions in the labor market, facing numerous forms of racial, gender, and class discrimination. Data from IBGE and DIEESE indicate that these women have the highest rates of unemployment, informality, and underutilization of the workforce, in addition to having the lowest average monthly incomes, even among those with a college degree. The illiteracy rate, for example, among black and brown women is twice that of white women, and the same is true when we look at maternal mortality. Furthermore, it has been found that the myth of racial democracy acts as an ideological mechanism that masks such inequalities, promoting the false ideal of harmonious coexistence and equal opportunities among racial groups. A comparison between empirical data and theories of racial democracy, such as those proposed by Gilberto Freyre and criticized by Florestan Fernandes, reveals that this ideology serves to perpetuate the denial of structural racism in Brazil. Thus, the socioeconomic inclusion of black women in Brazil not only dismantles this myth, but also exposes the limitations of public policies and institutional structures in
The socioeconomic insertion of black women in Brazil and the myth of racial democracy
Keywords: Democracia racial; Mulheres negras; Racismo; Mercado de trabalho; Racial democracy; Black women; Racism; Labor market; CIENCIAS SOCIAIS APLICADAS